2017
DOI: 10.1002/app.45680
|View full text |Cite
|
Sign up to set email alerts
|

Temperature scanning stress relaxation measurements: A unique perspective for evaluation of the thermomechanical behavior of shape memory polymer blends

Abstract: Shape memory polymer has the inherent capability of fixing its shape to a deformed or unconstrained shape that gives the material shape fixity and to revert back to its permanent shape that results shape recovery of the material. Temperature scanning stress relaxation (TSSR) studies of uncrosslinked and radiation crosslinked polymer blends of ethylene octene copolymer and ethylene propylene diene rubber has been carried out over a certain temperature range that gives the idea about the thermomechanical behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…The yellow and brown regions illustrate the existence of hard phase (EOC phase) and soft phase (EPDM phase), respectively. [ 43,44 ] The phase images of the EO 50 EP 50 blend shows that both the hard and soft phases are continuous and there is a uniform distribution of the hard and soft phases.…”
Section: Resultsmentioning
confidence: 99%
“…The yellow and brown regions illustrate the existence of hard phase (EOC phase) and soft phase (EPDM phase), respectively. [ 43,44 ] The phase images of the EO 50 EP 50 blend shows that both the hard and soft phases are continuous and there is a uniform distribution of the hard and soft phases.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-link density is one of the most dominant factors on stress relaxation of elastomers. From this point of view, cross-link densities of the original vulcanizates (before aging) have been calculated using initial slope values of their non-isothermal relaxation curves according to rubber elasticity theory, 22,[26][27][28][29][30] and the results are given in Table 5. Equivalent calculations were performed for aged vulcanizates, and the results are given in Table 6.…”
Section: Tssr Studymentioning
confidence: 99%
“…To the date, only a limited number of studies have been reported employing TSSR to investigate TPEs. Chatterjee et al [15] used TSSR as a unique method to examine the thermomechanical behavior of shape memory polymer blends based on radiation crosslinked ethylene octene copolymer and ethylene propylene diene rubber blends. Increase in TSSR index and crosslink density (CLD) gave a direct idea of the improved elasticity in the system with radiation curing.…”
Section: H Tmentioning
confidence: 99%
“…The test was carried out in a TSSR instrument (Brabender GmbH, Duisberg, Germany, which is commercially available). [9,11,12,15] The TSSR instrument is equipped with an electrical heating chamber in which the sample to be tested is positioned between two clamps. A definite uniaxial extension was applied to the sample through a linear drive unit connected to the clamps.…”
Section: Temperature Scanning Stress Relaxationmentioning
confidence: 99%
See 1 more Smart Citation